A comprehensive work up of various ventricular tachy-arrhythmias in relation to the underling cardiac disorder / status - Patra, Tusharkanti; Kumar, Prashant; Mukherjee, Somnath; Passi, Anurag; Islam, S. K. Saidul (International Journal of Research in Medical Sciences, 2017)
Background: Main objective of the study is details work up of the patients of ventricular tachy-arrhythmias and to find out its association with any structural heart disease. Methods: This institution based observational study was conducted in patients of documented sustained VT (ventricular tachycardia) with consecutive 102 patients. Results: The mean age of the VT patients was 56.7 years and the number of male patients were 70 (69%). In our study, among 102 patients 45 patients were diabetic, 64 patients were hypertensive, 30 patients were current smoker, family history of heart disease was present in 25 patients and family history of SCD (sudden cardiac death) was present in 5 patients. Among the patients who presented with symptoms of ventricular tachy arrhythmia, 25 patients had EF (ejection fraction) above 40%, 36 had EF between 31 to 40% and only 2 had EF below 30%. CAG (coronary angiography) done in 98 patients and 16 had normal coronaries. 20, 16 and 46 patients had single, double and triple vessel disease respectively. 80 patients had coronary heart disease (78%), 20 patients among them had acute ischemic events and 60 had chronic ischemic disease. 12 patients didn’t have any structural heart disease. Conclusions: Ischemic heart disease, acute or chronic, is the most common causes of ventricular tachyarrhythmia. male sex, diabetes mellitus, hypertension, smoking, family history of heart diseases or sudden cardiac death being the risk factors of coronary artery disease are also predisposing factors of ventricular tachyarrhythmia.